Safety and Efficacy of Bleb Needling with Antimetabolite after Trabeculectomy Failure in Glaucoma Patients: A Systemic Review and Meta-Analysis - Xuhao Chen; Lingge Suo; Ying Hong; Chun Zhang (Journal of Ophthalmology)
Background. Bleb needling with subconjunctival injection of antimetabolites had become a widely accepted approach for trabeculectomy failure. However, IOP reduction effects, success rates, and complications occurrence for this procedure showed great inconsistency among the different studies. Methods. We conducted a literature search on PubMed, Embase, Cochrane Library, and ClinicalTrials.gov. A random-effects model was performed on the extracted data based on the included studies. The intraocular pressure (IOP) and number of antiglaucomatous medications before and after the surgery were pooled for meta-analysis. The success and complication rates were estimated based on the results. Subgroup analysis, sensitivity analysis, and metaregression were applied to explore the origination of heterogeneity. Results. Thirty-seven studies with a total of 2182 patients were finally included in our review. For the present meta-analysis, the overall effects of bleb needling at the last visit revealed a reduction in IOP of 9.74 mmHg (95% confidence interval (CI) [8.85, 10.63]), 45.9% (95% CI [39.0%, 53.0%]) for complete success rate, and 70.4% (95% CI [63.5%, 77.0%]) for qualified success rate. Application of mitomycin C (MMC) and 5-fluorouracil (5-Fu) during the procedure were efficacious for IOP control during the follow-up. Metaregression revealed that possible origination of heterogeneity was baseline IOP before bleb needling, revealing a trend that higher baseline IOP correlated with a greater IOP reduction results p<0.001. For safety profile, conjunctival haemorrhage (5.7%, 95% CI [2.5%, 10.1%]), hyphema (5.5%, 95% CI [3.0%, 8.7%]), and bleb leakage (5.0%, 95% CI [3.2%, 7.3%]) had the highest estimate of incidence. An increasing number of needling was the main risk factor for needling failure. Conclusion. Bleb needling with antimetabolites could be considered an effective and safe procedure after trabeculectomy failure. After the process, patients will gain IOP control and reduce antiglaucomatous medications for at least six months with 5-Fu or MMC. Meanwhile, the overall estimates for complications were relatively low in the whole process.